2021
DOI: 10.3390/jof7020088
|View full text |Cite
|
Sign up to set email alerts
|

Autopsy Proven Pulmonary Mucormycosis Due to Rhizopus microsporus in a Critically Ill COVID-19 Patient with Underlying Hematological Malignancy

Abstract: Viral infections can cause acute respiratory distress syndrome (ARDS), consequently leading to susceptibility for secondary pulmonary infections. Over the past few weeks, a number of studies have reported on secondary pulmonary aspergillosis complicating severe COVID-19. We report the case of a 53-year old male patient with secondary acute myeloid leukemia (AML) who suffered from COVID-19 ARDS and was diagnosed postmortem with mucormycosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
76
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 9 publications
3
76
0
5
Order By: Relevance
“…Due to negative testing of fungal infections the patient was not treated with any other azoles except voriconazole, an antifungal used a prophylaxis in such patients. This report was also intended to raise awareness for early detection and treatment of mucormycosis 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Due to negative testing of fungal infections the patient was not treated with any other azoles except voriconazole, an antifungal used a prophylaxis in such patients. This report was also intended to raise awareness for early detection and treatment of mucormycosis 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Rhino-orbital mucormycosis The study recommends mycotic infection in COVID-19 patients with diabetes Waizel-Haiat et al, 2021 49-year-old male fever, cough, and shortness of breath Chest X-ray RT-PCR ceftriaxone and azithromycin, enoxaparin, remdesivir COVID-19 infection and necrotic empyema with mucormycosis Immunocompromised condition developed with fungal infection Placik et al, 2020 53-year old male acute myeloid leukemia, myelodysplastic syndrome, obesity and depression sore throat, parageusia, dysosmia and fever RT-PCR Chest X-ray BAL and PAS Corticosteroids and antibacterial therapy COVID-19 positive BAL showed mixed nonpathogenic flora. Lungs observed with Rhizopus microsporus COVID-19 ARDS with acute myeloid leukemia was observed with mucormycosis in postmortem Zurl et al (2021) 66-year-old male Diabetes mellitus KOH mount COVID-19 with ophthalmoplegia. Rhino-orbital cellulitis with ischemia This was the first study with orbital infarction syndrome in COVID-19 patient Rao et al, 2021 56-year-old man Renal disease fatigue and shortness of breath Chest X-ray RT-PCR GMS and pleural fluid culture CT scan MALDI-TOF methylprednisolone and tocilizumab COVID-19 with mucormycosis Higher mortality rate in COVID-19 with mucormycosis Kanwar et al (2021) 31 patients Different diseases ...…”
Section: Possible Role Of Action Of Mucormycosis Among Covid-19 Patientsmentioning
confidence: 99%
“…4 ). Similarly, a patient with acute myeloid leukemia (AML) also suffered mucormycosis after the COVID-19 infection ( Zurl et al, 2021 ). Although these factors such as diabetes, organ transplantation and hematological factors are commonly linked to mucormycosis, it is evident that COVID-19 infection also acts as a trigger in these situations.…”
Section: Covid-19 and Mucormycosis: A Tangled Relationmentioning
confidence: 99%
“…The increasing number of recent case series of mucormycosis complicating COVID-19 patients in the United States, 10 16 Austria, 17 Brazil, 18 Mexico, 19 Italy, 20 France, 21 Iran, 22 – 24 and India, 25 34 raises concerns regarding the misuse of immunosuppressive drugs in patients with COVID-19. Mucormycosis is a neglected mycosis that should be considered in the context of patients with COVID-19, in the same way as COVID-19 associated pulmonary aspergillosis, and it is possibly underreported.…”
mentioning
confidence: 99%
“… 22 , 37 There is an urgent need to reconsider the careful use of these drugs in patients with severe COVID-19 due to the high prevalence of underlying comorbidities in these patients, 11 13 , 25 , 28 30 including diabetes mellitus, 13 , 16 , 19 , 26 , 28 30 hematological malignancies (i.e. acute myeloid leukemia), 17 end-stage kidney disease, 27 and organ transplant recipients. 15 A recent review of published cases found eight reports 27 where diabetes mellitus was the most common risk factor for the development of mucormycosis.…”
mentioning
confidence: 99%